Analysis of Accounting Information Systems in Islamic Perspective - Divya Prihatiningrum; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
SIA (Accounting Information System) is a system that collects, stores, and processes financial and accounting data used by decision makers. The purpose of this study was to determine the accounting system in the Islamic perspective at the Syariah Bank branch of BNI Syariah Jalan Gajah Mada no. 179, Panjunan Bulusidokare Sidoarjo in accordance with Islam and to find out the accounting system at the Sharia Bank branch of BNI Syariah Jalan Gajah Mada no. 179, Panjunan Bulusidokare Sidoarjo in accordance with Islam. This study uses a qualitative approach. The method used in this research is descriptive method. The data source used in this study is the primary data source obtained from BNI Syariah Sidoarjo branch. While the secondary data sources were obtained from direct interviews with BNI Syariah employees. While the data collection methods used are observation, interviews, and documentation. Furthermore, the data analysis techniques used are data collection, data reduction, and data verification. The results of the study note that the accounting information system in the Islamic perspective at BNI Syariah is the activities of recording, collecting, collecting funds and distributing funds using sharia principles contained in Islamic values.